THE ABUNDANCES IN THE STELLAR ATMOSPHERES IN THE M13 GLOBULAR CLUSTER - Mishenina, T. V.; Kutsenko, S. V. (Одеські астрономічні публікації, 2017)
The chemical composition of 5 stars' atmospheres in globular cluster M13 and 2 halo stars taken from literature have been computed. A slight excess of O and deficit of Mg have been defined for globular cluster stars. The elements Si, Ca, Ti are overabundant (≈ 0.3 dex), Ni is slightly deficient (-0.08), Mg - more deficient (- 0.3), Y - slightly overabundant. Comparison with halo stars showed the difference in composition of Na, Mg and elements of r-, s- processes.